Effect of native and allochthonous arbuscular mycorrhizal fungi on Casuarina equisetifolia growth and its root bacterial community. Issue 2 (3rd April 2018) - Diagne, Nathalie; Baudoin, Ezékiel; Svistoonoff, Sergio; Ouattara, Christine; Diouf, Diegane; Kane, Aboubacry; Ndiaye, Cheikh; Noba, Kandioura; Bogusz, Didier; Franche, Claudine; Duponnois, Robin
ABSTRACT: Exotic trees are often planted to recover degraded lands. Inoculation with mycorrhizal fungi can improve their survival. Plant growth is partly dependent on the strain used, but little attention has been paid to the selection of mycorrhizal fungi. The aim of this study was to determine whether the growth of Casuarina equisetifolia L. (Johnson) is affected by two different mycorrhizal inocula generated using fungal spores retrieved from an Australian site (allochthonous soil) and a Senegalese site (native soil) under C. equisetifolia trees. Comparative experiments were conducted with plants in a Senegalese soil, previously sterilized or not, and grown in a greenhouse. At harvest, parameters related to plant growth and mycorrhization were evaluated and soil bacterial communities were compared. Tree growth was significantly influenced by both types of inoculants. In unsterilized soil, plants inoculated with the native inoculant were taller than plants inoculated with the allochthonous inoculant and control plants. The frequency of mycorrhization with both inoculants was higher in unsterilized soil. The strongest effects of the mycorhizosphere on the soil microbiome were obtained with the allochthonous inoculum, and analysis of the taxonomic composition revealed mycorrhizal communities specific to each inoculum. These results suggest that the development of C. equisetifolia and its root bacterial community are dependent on the composition of the mycorrhizal inoculum. The functional consequences of this rhizosphere effect in terms of soil fertility should be further studied to better guide reforestation operations.